2022
DOI: 10.1155/2022/1544244
|View full text |Cite
|
Sign up to set email alerts
|

TRPV1 Modulator Ameliorates Alzheimer-Like Amyloid-β Neuropathology via Akt/Gsk3β-Mediated Nrf2 Activation in the Neuro-2a/APP Cell Model

Abstract: Alzheimer’s disease (AD) is a progressive and irreversible neurodegenerative disorder for which there is no effective therapeutic strategy. PcActx peptide from the transcriptome of zoantharian Palythoa caribaeorum has recently been identified and verified as a novel antagonist of transient receptor potential cation channel subfamily V member 1 (TRPV1). In the present study, we further investigated the neuroprotective potential of PcActx peptide and its underlying mechanism of action, in an N2a/APP cell model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 70 publications
3
1
0
Order By: Relevance
“…AKT1 phosphorylation (pAKT1) was significantly increased (P < 0.01) in the organ of Corti lysates from animals cotreated with kanamycin and PL compared with the rest of the groups. These results are in accordance with previous studies showing the protective effect of AKT activation against neurodegenerative disorders (35) and the modulation of AKT's activity by PL (23).…”
Section: Pl's Role In the Transient Receptor Vanilloid 1/akt1 Pathwaysupporting
confidence: 93%
See 2 more Smart Citations
“…AKT1 phosphorylation (pAKT1) was significantly increased (P < 0.01) in the organ of Corti lysates from animals cotreated with kanamycin and PL compared with the rest of the groups. These results are in accordance with previous studies showing the protective effect of AKT activation against neurodegenerative disorders (35) and the modulation of AKT's activity by PL (23).…”
Section: Pl's Role In the Transient Receptor Vanilloid 1/akt1 Pathwaysupporting
confidence: 93%
“…Thus, the constant binding of PL to TRPV1's allosteric site may have a twofold effect; initially, it blocks activity, but, eventually, it will decrease surface expression. The link between TRPV1 activation and AKT1 inhibition has previously been shown (35). In the present work, we found that (i) pAKT1 is reduced during kanamycin treatment (kinome, immunohistochemistry, and immunoblot assays) and (ii) treatment with PL or absence of TRPV1 results in a modest, but significant (P < 0.05), activation of AKT1.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Apart from being as a kinase involved in tau phosphorylation and the production of A␤ [56,57], GSK-3␤ has a role in keeping homeostasis of neural progenitor in the rodent brains during the early developmental period [58]. In our preceding scholarly publication, the impact of GSK-3 activation or inhibition on neurogenesis was examined [59,60].…”
Section: Discussionmentioning
confidence: 99%